Effect of a high-fat meal on the relative bioavailability of H3B-6527, a novel FGFR4 inhibitor, in healthy volunteers - Rioux, Nathalie; Kim, Amy; Nix, Darrell; Bowser, Todd; Warmuth, Markus; Smith, Peter G.; Schindler, Joanne (Cancer chemotherapy and pharmacology, 2019)
Purpose This Phase I study estimated the effect of a high-fat meal on the pharmacokinetics (PK) of H3B-6527, a covalent inhibitor of the fibroblast growth factor receptor (FGFR) 4 in clinical development for hepatocellular carcinoma and intrahepatic cholangiocarcinoma. Methods In this randomized, single center, single-dose, open-label, 2-period crossover study 12 healthy male volunteers, aged 18–55 years old, received a single 200-mg dose of H3B-6527 (capsule) following an overnight fast or a high-fat breakfast. PK samples were collected serially up to 36 h postdose. H3B-6527 concentrations were measured using a validated high-performance liquid chromatography tandem mass spectrometry method. PK data were analyzed using a noncompartmental approach based on a mixed-effects model. The safety and tolerability of H3B-6527 were also assessed. Results H3B-6527 plasma exposure increased after a high-fat meal with fed/fasted ratios of the geometric means (90% confidence interval) of 174% (102–298%) for C max and 246% (146–415%) for AUC 0– t . Food delayed and prolonged absorption of H3B-6527, with a fed/fasted ratio for t max of 200% (137–263%). PK variability was lower under the fed condition, as illustrated by the CV% for C max and AUC 0– t of 41.9–54.5% (fed) versus 64.3–70.4% (fasted). Conclusions A single 200 mg dose of H3B-6527 was safe and generally well tolerated when administered to healthy adult males. A high-fat meal significantly increased exposure to H3B-6527, from 1.5- to 2.5-fold in the systemic circulation, compared to administration under fasted conditions. Food delayed and prolonged absorption of H3B-6527. In general, lower inter-subject variability was observed in the fed state in healthy volunteers. Trial registration ClinicalTrials.gov.: NCT03424577.